2015
DOI: 10.4329/wjr.v7.i12.494
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of serum testosterone following neoadjuvant and adjuvant androgen deprivation therapy in men treated with prostate brachytherapy

Abstract: Lower T levels at cessation of ADT were associated with prolonged T recovery in the long-term usage group. Five years after cessation of long-term ADT, approximately one-fifth of patients still had castrate T levels. When determining the therapeutic effect, especially biochemical control, we should consider this delay in T recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…We did not eliminate those influences of stage migration on the prognostic value. Second, technical modifications for the radiotherapy, different duration of neoadjuvant ADT, different types of nonsteroidal anti‐androgen agents, and sustained castration testosterone levels after cessation of long‐term ADT may have influenced the interpretation of the data . Third, patients who were diagnosed before the 2005 ISUP consensus conference was proposed were included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not eliminate those influences of stage migration on the prognostic value. Second, technical modifications for the radiotherapy, different duration of neoadjuvant ADT, different types of nonsteroidal anti‐androgen agents, and sustained castration testosterone levels after cessation of long‐term ADT may have influenced the interpretation of the data . Third, patients who were diagnosed before the 2005 ISUP consensus conference was proposed were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, technical modifications for the radiotherapy, 31 different duration of neoadjuvant ADT, different types of nonsteroidal anti-androgen agents, and sustained castration testosterone levels after cessation of long-term ADT may have influenced the interpretation of the data. 32 Third, patients who were diagnosed before the 2005 ISUP consensus conference was proposed were included in this study. Although our pathologists never assigned a Gleason score of 2-4 for the biopsy specimens and were early adopters of the grading system, Gleason grade migration was likely to occur in some patients as a result of the proposal.…”
Section: Comparisons Of the Clinical Features Between Patients With Ct3bmentioning
confidence: 99%
“…This is considered to occur because the feedback system of the hypothalamic–pituitary axis responded normally to the low TST levels after termination of ADT. Past studies reported that older age was a significant factor associated with slower TST recovery . Other studies showed that the production of TST decreases with age .…”
Section: Discussionmentioning
confidence: 97%
“…Past studies reported that older age was a significant factor associated with slower TST recovery. 14,16,17 Other studies showed that the production of TST decreases with age. 18,19 This decline might be related to later TST recovery in older men treated with ADT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation